2011
DOI: 10.1007/s10916-010-9637-2
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects and Safety of Magnetic Resonance Imaging

Abstract: Dear Sir, With interest we took note of a review on health effects and safety of Magnetic Resonance Imaging by Drs Ng, Faust and Acharya U, published online on March 30 2010 in the Journal of Medical Systems [1]. As adequately described by the authors there are a wide number of advantages to the use of MRI as a medical imaging modality that have led to improved diagnostic outcomes without the drawbacks of for example the use of X-rays; hence the exponential growth in usage since its first introduction in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Acute symptoms and neurocognitive effects have been reported to be associated with exposure to MRI‐related SMF and time‐varying magnetic fields, mainly among workers in MRI‐production, and to a limited extent, among imaging workers in healthcare . Hardly any data are available on effects of long‐term occupational exposure to SMF , but considering the nature of reported acute effects on balance , visual perception and hand–eye coordination , the question was raised whether long‐term SMF exposure may lead to increased risk of work‐related accidents, commute‐related (near) accidents, and accidents in general.…”
Section: Introductionmentioning
confidence: 99%
“…Acute symptoms and neurocognitive effects have been reported to be associated with exposure to MRI‐related SMF and time‐varying magnetic fields, mainly among workers in MRI‐production, and to a limited extent, among imaging workers in healthcare . Hardly any data are available on effects of long‐term occupational exposure to SMF , but considering the nature of reported acute effects on balance , visual perception and hand–eye coordination , the question was raised whether long‐term SMF exposure may lead to increased risk of work‐related accidents, commute‐related (near) accidents, and accidents in general.…”
Section: Introductionmentioning
confidence: 99%
“…We performed measurements at the hip, which was done so that wearing the dosimeter would not interfere with participants' work, but as outlined above this may have underestimated exposure to the head, which is generally considered the target organ for the observed effects. 37 We opted not to measure nearer the head, for example, at the chest as was done in the Dutch study, 29 because it is fairly unlikely that if in the future routine monitoring of staff is introduced, it will be carried out using relatively inconvenient protocols. Nonetheless, as it is difficult to determine whether the location of the dosimeter at the hip systematically overestimates or underestimates exposure measured at the chest, future work will need to assess correlations of exposures measured at different places on the body during simultaneous measurements of different movement patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in high Tesla environments, high dB / dt levels could likely be produced at the vestibular system level. This explains why moving outside the bore generates stronger dB / dt values than the ones obtained within the bore (Fuentes et al, 2008; Kännälä et al, 2009; De Vocht et al, 2012). Fuentes et al (2008) have found peak dB / dt of 7.3 T/s obtained by normal body movements within a 1.5 MRI scanner environment.…”
Section: Moving Forwardmentioning
confidence: 95%